Whithering Punjab agriculture: Can it regain its leadership - International Food Policy Research Institute (International Food Policy Research Institute, 2007)
Punjab agriculture was an undisputed leader in the Green Revolution in India and the Punjab farmer was acclaimed worldwide. But today Punjab agriculture no longer calls the shots, nor does it play the leadership role that others would want to emulate. The Punjab agricultural sector has reached a point where it must make significant changes if it wants to move forward and regain its leadership role. Conversely, if the state does not rationalize incentives, create new institutions and reinvigorate old ones, and increase investments significantly, it will suffer declining income and employment and irreversible environmental degradation.